Continuous and multiple waves of emotional responses: Mother's experience with a premature infant - Valizadeh, Laila (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: In recent years, there has been a rise in the number of premature births. Mothers of these newborns experience a high degree of stress over time. Since a more comprehensive understanding of this phenomenon can help the healthcare teams in detecting the deficiencies and needs of such newborns’ mothers for a better and more effective intervention, the present study was carried out to describe the mothers’ experiences in the area of premature birth. MATERIALS AND METHODS: The present study is a qualitative study with a content analysis approach. The data collection process included 15 semi-structured and in-depth interviews with the mothers delivering premature babies during 2012-2013 in the medical educational centers of north and northwest of Iran. A purposive sampling method was used. All the interviews were recorded, typed, and finally analyzed using a qualitative content analysis with a conventional method. RESULTS: Data analysis led to the extraction of continuous and multiple waves of emotional responses in mothers with premature birth. This has been revealed in mothers by the different categories of affective reactions, symptoms of anxiety, and mood disturbances including decline in performance, individual shortcomings, and mental irritation. CONCLUSIONS: Mothers’ unpreparedness and unexpected childbirth make them encounter the multiple and continuous waves of emotional responses, which will consequently lead to decline in performance, individual shortcomings, and mental irritation among them. Therefore, in order to prevent the negative and long-term consequences of such reactions, it is recommended that more attention should be given to support these mothers as the main caregivers of such infants.